2018
DOI: 10.1097/ogx.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Use and Ovarian Cancer Risk: An Analysis in the Ovarian Cancer Cohort Consortium

Abstract: with AHA, ACOG has alerted OB/GYN specialists and subspecialists to pay attention to one of the most important threats to women's health. The risk assessment and counseling steps being advocated are straightforward. The AHA's Life's Simple 7 tool can be completed by patients before their visits (even privately in the waiting room). The results can identify patients' specific risks to enable efficient use of the face-to-face visit. Fortunately, even brief messages from physicians repeated over time can be effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Chronic inflammation was hypothesized as a mechanism of ovarian carcinogenesis in a seminal paper by Ness and Cottreau (2), which has been supported by growing epidemiologic evidence. Conditions of chronic inflammation, such as endometriosis and pelvic inflammatory disease, are risk factors for ovarian cancer (3,4), while anti-inflammatory exposures, such as aspirin use, are associated with a decreased risk (5)(6)(7). "Incessant ovulation" (8), which links physiologic damage of the ovarian surface epithelium during ovulation to an increase in inflammatory mediators (e.g., cytokines, prostaglandins) that can enhance tumorigenesis, is further implicated in ovarian cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation was hypothesized as a mechanism of ovarian carcinogenesis in a seminal paper by Ness and Cottreau (2), which has been supported by growing epidemiologic evidence. Conditions of chronic inflammation, such as endometriosis and pelvic inflammatory disease, are risk factors for ovarian cancer (3,4), while anti-inflammatory exposures, such as aspirin use, are associated with a decreased risk (5)(6)(7). "Incessant ovulation" (8), which links physiologic damage of the ovarian surface epithelium during ovulation to an increase in inflammatory mediators (e.g., cytokines, prostaglandins) that can enhance tumorigenesis, is further implicated in ovarian cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…women <70 years). In contrast, a pooled analysis of cohort studies reported a more modest inverse association for daily aspirin (pooled HR 0.90 [0.82-1.00]) and no association for low-dose aspirin (pooled HR 0.99 [0.79-1.23]), though few included studies had data on aspirin dose [3]. These studies assessed aspirin use at baseline only (with mean baseline age ranging from 46-64 years), and may have misclassified aspirin use at older ages, more proximal to ovarian cancer diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…We leveraged data from a large cohort, though we still had limited power to examine associations for the rare outcome of ovarian cancer, particularly when we stratified by age and divided our exposed population into finer categories of aspirin use. Due to limited power, we were unable to examine associations by ovarian cancer histotype, though there has not been substantial etiologic heterogeneity by histotype in prior analyses [2,3]. We were also unable to disentangle the effects of low-dose aspirin use from daily aspirin use since dose and frequency of use are highly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…studies supported the potential benefits of NSAIDs in the prevention and treatment of several cancers, including colon, 4,75,76 ovarian, 7 breast, 8,9 lung, 10 and prostate. 11 In this context, long-term use of aspirin reduces the risk of colorectal, 4,77−80 ovarian, 7,81 breast, 82 and prostate cancer 83 and hepatocellular carcinoma. 84,85 Further, almost 90 clinical trials involving aspirin are being or have been carried out, such as the randomized phase II trial that demonstrated aspirin's pharmacological efficacy in preventing colorectal cancer in patients at increased risk of colorectal cancer.…”
Section: Clinical Studies Several Epidemiological and Clinicalmentioning
confidence: 99%